Introducing carbon taxes in South Africa - Alton, Theresa; Arndt, Channing; Davies, Rob; Hartley, Faaiqa; Makrelov, Konstantin; Thurlow, James; Ubogu, Dumebi (Elsevier, 2014)
South Africa is considering introducing a carbon tax to reduce greenhouse gas emissions. Following a discussion of the motivations for considering a carbon tax, we evaluate potential impacts using a dynamic economywide model linked to an energy sector model including a detailed evaluation of border carbon adjustments. Results indicate that a phased-in carbon tax of US$30 per ton of CO2 can achieve national emissions reductions targets set for 2025. Relative to a baseline with free disposal of CO2, constant world prices and no change in trading partner behavior, the preferred tax scenario reduces national welfare and employment by about 1.2 and 0.6 percent, respectively. However, if trading partners unilaterally impose a carbon consumption tax on South African exports, then welfare/employment losses exceed those from a domestic carbon tax. South Africa can lessen welfare/employment losses by introducing its own border carbon adjustments. The mode for recycling carbon tax revenues strongly influences distributional outcomes, with tradeoffs between growth and equity.